Improving the Personnel Motivation System in an Organization (on the Example of Qingdao HX University) - Tang, Nailing (Kharkiv : V. N. Karazin Kharkiv National University, 2024)
The master’s thesis examines theoretical and practical aspects of forming a motivation system for university teachers based on the case of HX University. The study explores key motivation theories, principles of incentive mechanisms, and modern approaches to human resource management in higher education. An analysis of the existing teacher motivation system is conducted, identifying its shortcomings and influencing factors. An improved incentive model is proposed, combining material and non-material motivation methods aimed at enhancing teaching performance and supporting university development.

У магістерській роботі досліджено теоретичні та практичні аспекти формування системи мотивації викладачів у закладах вищої освіти на прикладі HX University. Розглянуто основні теорії мотивації, принципи побудови стимулюючих механізмів та сучасні підходи до управління персоналом у сфері освіти. Проведено аналіз чинної системи мотивації викладачів, виявлено її недоліки та фактори впливу. Запропоновано удосконалену модель стимулювання, що поєднує матеріальні та нематеріальні методи мотивації, спрямовану на підвищення ефективності роботи викладачів і розвитку університету.
Удосконалення системи мотивації персоналу в організації (на прикладі університету Qingdao HX)
Керівник роботи: Ганна Петрівна Рекун, кандидат економічних наук, доцент кафедри управління та адміністрування, Навчально-науковий інститут "Каразінська школа бізнесу"
Keywords: SOCIAL SCIENCES::Business and economics::Business studies; staff motivation; мотивація персоналу; personnel management; управління персоналом; менеджмент персоналу; personnel training; навчання персоналу